Work, learning and customs in historical perspective: Education and work in the nineteenth century - Fred M. Schied (Adult Education Research Conference, 1993)
This paper discusses the connection between custom and self-education in early nineteenth century United States. The paper argues that the control of education was of fundamental concern to working people in the early labor movement.